Three-year follow-up in a subset of high-risk patients randomly assigned to off-pump versus on-pump coronary artery bypass surgery: the Best Bypass Surgery Trial. Issue 11 (17th March 2011) - Møller, Christian H; Perko, Mario J; Lund, Jens T; Andersen, Lars W; Kelbæk, Henning; Madsen, Jan K; Winkel, Per; Gluud, Christian; Steinbrüchel, Daniel A
Abstract : Objective: To evaluate off-pump versus on-pump coronary artery bypass grafting (CABG) in patients with three-vessel disease and a high-risk operative profile. Design: A randomised clinical trial. Setting: Rigshospitalet, University Hospital, Copenhagen, Denmark. Participants: 341 patients with three-vessel disease and a EuroSCORE of 5 or greater. Main exclusion criteria were previous heart surgery, poor left ventricular function (ejection fraction <30%), or unstable preoperative condition. Intervention: CABG performed with versus without cardiopulmonary bypass. Main outcome measure: The primary outcome was a composite of major adverse cardiac and cerebrovascular events (MACCE) including all-cause mortality, acute myocardial infarction, cardiac arrest with successful resuscitation, low cardiac output syndrome/cardiogenic shock, stroke and coronary reintervention. Results: MACCE occurred in 69 (40%) patients allocated to off-pump versus 54 (33%) patients allocated to on-pump CABG during the median 3.7 years of follow-up (HR 1.22; 95% CI 0.86 to 1.75; p=0.26). All-cause mortality was significantly increased in the off-pump group (24% vs 15%; HR 1.66, 95% CI 1.02 to 2.73; p=0.04), but cardiac-related death was not significantly different (10% vs 7%; HR 1.30, 95% CI 0.64 to 2.66; p=0.47). An insignificant trend towards a reduction in myocardial infarction after off-pump CABG was observed (7% vs 14%; HR 0.53, 95% CI: 0.27 to 1.04; p=0.06). Conclusions: No significant difference in the primary outcome of MACCE was found between off-pump and on-pump CABG. However, mortality seemed higher after off-pump CABG. Trial registration: http://clinicaltrials.gov/ number, NCT00120991 .